Method for suppressing seismic exploration random noise based on frequency slice time-frequency peak filtering - GONG ZIHUI; LI GUANGHUI; FENG ZHIQIANG; LIANG MEIYAN (2020)
The invention relates to a method for suppressing seismic exploration random noise based on frequency slice time-frequency peak filtering. The method comprises the following steps: converting the noise-containing signal of the time domain into a noise-containing signal of a frequency domain space, slicing the noise-containing signal in the frequency domain space, dividing the noise-containing signal into a plurality of frequency slices with any length, determining the main frequency and the filtering window length of each frequency slice, performing time-frequency peak filtering on each frequency slice, and finally superposing the filtered time domain signal components to obtain a filtered signal. According to the method, the frequency slice and the time-frequency peak filtering TFPF are combined, the TFPF can be effectively helped to select the optimal filtering window length for signals of different main frequencies through slice processing, and the problem that the TFPF cannot use self-adaptive window leng